The Efficiency of Waste Materials in Eco - Concrete - Abu Bakar, Nor Hidayah; Idres, Faizzul Fikri; Kamri, Nurul Ayuni; Ahmad, Nor Farah Atiqah (Multidisciplinary Applied Research and Innovation, 2022)
Eco concrete is a building material that is used a composite man made material and mix with waste material. It is well known research in order to reduce the waste material in the environment. Waste material that used are Poly Ethylene Terephethalate (PET), fly ash, rice husk and waste glass. This study focuses on the how effective the waste materials applied in the Eco concrete and will it be good enough to use in construction industry. Mechanical properties will be as a benchmark to compare all the waste material in this study. Maximum researched paper for this study is 30 papers and using critical review to point out what is the best or the optimal percentage waste material used in Eco concrete. The range of research paper used is 2003 until 2021. To be assumed different optimal percentage can be studied for maximizing the usefulness of each waste material that can be used in real construction. The most studied waste material in the range year is waste glass and although its optimal percentage is different by each researched paper, it still can be considered to use in real construction because of its own mechanical properties.